2021
DOI: 10.1002/jmri.27917
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Analysis of Kidney Injury in Rats With Cirrhosis Induced by Common Bile Duct Ligation Using Arterial Spin Labeling MRI

Abstract: Background Arterial spin labeling (ASL) has been proven to be effective in ischemia‐induced acute kidney injury (AKI); however, validation of ASL magnetic resonance imaging (MRI) is limited in AKI in the presence of cirrhosis. Purpose To investigate the feasibility of ASL in revealing renal blood flow (RBF) changes in kidney injury in the presence of cirrhosis and to assess its value in the early diagnosis of disease. Study Type Longitudinal. Animal Model Rats were randomized into baseline group (N = 3), sham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A previous study ( Wei et al, 2019 ) reflected that renal function showed no dominant reduction after CIRI only judged by Scr and BUN contents. This was mainly due to the strong compensatory function of the kidney and Scr exhibited abnormal only when more than half of the nephrons were impaired ( Yu et al, 2021 ). The correlation analysis showed no strong correlation between MRI parameters and Scr, BUN.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study ( Wei et al, 2019 ) reflected that renal function showed no dominant reduction after CIRI only judged by Scr and BUN contents. This was mainly due to the strong compensatory function of the kidney and Scr exhibited abnormal only when more than half of the nephrons were impaired ( Yu et al, 2021 ). The correlation analysis showed no strong correlation between MRI parameters and Scr, BUN.…”
Section: Discussionmentioning
confidence: 99%
“…With a hepatorenal syndrome rat model, Yu et al 9 demonstrate that tissue perfusion tracks serum and histological markers of AKI, from the onset of acute damage to recovery. In their comprehensive longitudinal dataset, the authors demonstrate that changes in kidney perfusion could be reliably quantified with ASL MRI.…”
mentioning
confidence: 99%